Impact of conversion from rice farms to oil palm plantations on socio-economic aspects of ex-migrants in Indonesia - Imron Zahri; Elisa Wildayana; Agus Thony Ak; Dessy Adriani; M. Umar Harun (Agricultural Economics (AGRICECON), 2019)
This paper aims to investigate the impact of land conversion from rice farming to oil palm plantations on the socio-economic aspects of ex-migrants in the South Sumatra tidal swamp, Indonesia. Land conversion from rice farming to oil palm plantations is a form of adaptation for ex-migrant farmers and will increase food deficits in Indonesia. Ex-migrant farmers initially cultivated food crops with conventional technology. This pattern has been changing, which have led to the formation of two large groups of farms, namely rice-based farms implementing mechanisation, and oil palm-based plantations. The results showed that changes from rice farming to oil palm plantations did not make the economy of farm households better. Between the two groups of farmers, there is no difference in arable land, the labour allocation for agriculture and the farmers' income. In addition, there is not much difference between farmers' participation in on-farm and out-farm activities. The area of arable land owned, the husbands'age, and family size variables are determinants of farmers' choice to participate in other jobs activities and influence farmers' income. Thus, changes in crops from rice to oil palm have no impact on cultivation area, labour allocation, income, on-farm and out-farm activities.